Prevalence and Risk Factors for Transient Osteoporosis of the Hip in Adult Osteogenesis Imperfecta Patients: A Cohort Retrospective Study - Harsevoort, Arjan; Vos, Bas; Edens, Mireille A.; Boomsma, Martijn F.; A.Franken, Anton; Janus, Guus J.M. (Archives of Clinical and Biomedical Research, 2020)
Purpose: Osteogenesis Imperfecta (OI) is a congenital disorder characterized by multiple fractures and a low bone mineral density (BMD). In our national OI expertise center for adults, we observed several cases of transient osteoporosis of the hip (TOH). The aim of this study was to report on the prevalence of TOH in adult OI patients, to identify possible additional risk factors and describe the natural history. Methods: The charts of 314 adult OI patients, seen on an outpatient base between January 2008 and January 2018, were reviewed for pain in the hip region. On the basis of pain with no reported trauma a Magnetic Resonance Imaging (MRI) was performed to identify patients with TOH and exclude other diseases. Additional risk factors were evaluated. Results: 5 of 314 (1.6%; 95% confidence interval 0.6% - 3.9%) OI patients showed TOH. There was a delay of 4-12 weeks between the start of the symptoms and the diagnosis of TOH. No additional risk factors were designated besides OI. Good clinical result by partial weight bearing in 4 patients, one patient received a total hip arthroplasty in a hospital in the surroundings of the patient. Conclusions: The prevalence of TOH in adult OIpatients is 1.6% in a ten years cohort. Due to the high prevalence, we recommend a MRI in OI-patients with pain in the hip region suspicious of TOH and inconclusive radiographs. No additional risk factors were noticed in our patient population for the development of TOH. The natural history is favorable by off-loading of the hip during the period of pain. We hypothesize that a mild degree of trauma causing microfractures could be the reason for bone marrow edema matching the clinical entity of TOH.